Rotational Energy Harvesting System: Power Conditioning, Controller and Observer Design - Ukoima K. N.; Ezeonye C. S., Uwaoma M. U., Chikere N. C. (Journal of Power Electronics and Devices, 2020)
This paper presents an analysis of the design of rotational energy harvesting systems. In this background a review of rotational structures is presented. Energy harvesting as a feedback problem is given. The methods of controller and observer designs are analyzed. Finally, the limitation of portable electrical energy is presented.